Employment of Filipinas as nannies in the context of post-socialist Czech Republic - Redlová, Pavla (Lidé města, 2013)
During the post-socialist development in the Czech Republic, many official and informal socio-cultural institutions have been reorganized: from the political and economical systems to gender and family relationships. The society became engaged in global processes, including migration and the global care market. Commodification and commercialization of domestic work have developed. Employment of Filipinas as nannies and housekeepers - although not statistically significant yet - represents a symptomatic example of the transformations and current development and a re-definition of a widespread social practice realized in many foreign countries. This paper presents an analysis of commodification of care. Specifically, I look at the ways intermediary agencies operate and how they approach potential customers offering care services of live-in Filipina nannies as a specific product with certain characteristics. I also focus on how the agencies construct the domestic work itself in order to examine whether it is recognized like any other work. The second part of the text deals with the working conditions as they are perceived by the nannies and with the nannies' position in the family, considered within the broader gender relations. The article is based both on qualitative interviews with agency representatives and with nannies and on an analysis of websites of intermediary agencies. Although the text is rather descriptive, it seeks to connect the Filipina domestic workers' employment with current socio-economic changes.